Key Ethical Issues in Pediatric Research: Islamic Perspective, Iranian Experience - Mobasher, Mina (Tehran University of Medical Sciences, 2012)
OBJECTIVE: The importance of pediatric research especially in the ethically proven trials resulted in considerable legislative attempts in association with compiling ethical guidelines. Because of children's vulnerability conducting pediatric research raises different ethical issues; the two most important of which are informed consent and risk-benefit assessment. Differences in religious and socio-cultural context limit implication of ethical standards. METHODS: At the aim of finding a solution we critically reviewed guidelines, and literatures as well as Islamic points in addition to comparing different viewpoints in application of ethical standards in pediatric research. FINDINGS: The literature review showed that pediatric research guidelines and authors’ viewpoints have the same basic ethical core, but there are some variations; depend on cultural, religious, and social differences. Furthermore, these standards have some limitations in defining informed consent according to child's age and capacity upon application. CONCLUSION: In this regard Islamic approach and definition about growth development and puberty sheds light and clarifies a clearer and more rational address to the issue.